Herbal Medicine in the Treatment of Premenstrual Syndromes - L Kashani; R Hajiaghaee; S Akhondzadeh (Institue of Medicinal Plants, ACECR, 2011)
Premenstrual syndromes (PMS) are a group of menstrually related, chronic and cyclical disorders characterized by emotional, behavioral, and physical symptoms in the second half (luteal phase) of the menstrual cycle. Several line of evidence point to a significant role of the serotonergic system in the course of the luteal phase in women with PMS/ Premenstrual Dysphoric Disorder. It has been reported that herbal medicine is useful in relieving the symptoms of PMS. An American telephone survey suggested that up to 80% self-medicating sufferers use complementary remedies. This review focused on herbal medicine in the treatment of PMS.